Protein stability regulators screening assay (Pro-SRSA): protein degradation meets the CRISPR–Cas9 library - Yuanzhong Wu; Tiebang Kang (Chinese Journal of Cancer, 2016)
Abstract The regulation of protein stability is a fundamental issue for biophysical processes, but there has not previously been a convenient and unbiased method of identifying regulators of protein stability. However, as reported in the article entitled “A genome-scale CRISPR–Cas9 screening method for protein stability reveals novel regulators of Cdc25A,” recently published in Cell Discovery, our team developed a protein stability regulators screening assay (Pro-SRSA) by combining the whole-genome clustered regularly interspaced short palindromic repeats Cas9 (CRISPR–Cas9) library with a dual-fluorescence-based protein stability reporter and high-throughput sequencing to screen for regulators of protein stability. Based on our findings, we are confident that this efficient and unbiased screening method at the genome scale will be used by researchers worldwide to identify regulators of protein stability.